Design and development of a peptide-based adiponectin receptor agonist for cancer treatment - Otvos, Laszlo (BioMed Central, 2011)
BACKGROUND: Adiponectin, a fat tissue-derived adipokine, exhibits beneficial effects against insulin resistance, cardiovascular disease, inflammatory conditions, and cancer. Circulating adiponectin levels are decreased in obese individuals, and this feature correlates with increased risk of developing several metabolic, immunological and neoplastic diseases. Thus, pharmacological replacement of adiponectin might prove clinically beneficial, especially for the obese patient population. At present, adiponectin-based therapeutics are not available, partly due to yet unclear structure/function relationships of the cytokine and difficulties in converting the full size adiponectin protein into a viable drug. RESULTS: We aimed to generate adiponectin-based short peptide that can mimic adiponectin action and be suitable for preclinical and clinical development as a cancer therapeutic. Using a panel of 66 overlapping 10 amino acid-long peptides covering the entire adiponectin globular domain (residues 105-254), we identified the 149-166 region as the adiponectin active site. Three-dimensional modeling of the active site and functional screening of additional 330 peptide analogs covering this region resulted in the development of a lead peptidomimetic, ADP 355 (H-DAsn-Ile-Pro-Nva-Leu-Tyr-DSer-Phe-Ala-DSer-NH(2)). In several adiponectin receptor-positive cancer cell lines, ADP 355 restricted proliferation in a dose-dependent manner at 100 nM-10 μM concentrations (exceeding the effects of 50 ng/mL globular adiponectin). Furthermore, ADP 355 modulated several key signaling pathways (AMPK, Akt, STAT3, ERK1/2) in an adiponectin-like manner. siRNA knockdown experiments suggested that ADP 355 effects can be transmitted through both adiponectin receptors, with a greater contribution of AdipoR1. In vivo, intraperitoneal administration of 1 mg/kg/day ADP 355 for 28 days suppressed the growth of orthotopic human breast cancer xenografts by ~31%. The peptide displayed excellent stability (at least 30 min) in mouse blood or serum and did not induce gross toxic effects at 5-50 mg/kg bolus doses in normal CBA/J mice. CONCLUSIONS: ADP 355 is a first-in-class adiponectin receptor agonist. Its biological activity, superior stability in biological fluids as well as acceptable toxicity profile indicate that the peptidomimetic represents a true lead compound for pharmaceutical development to replace low adiponectin levels in cancer and other malignancies.